Formation of double-shelled zinc-cobalt sulfide dodecahedral cages from bimetallic zeolitic imidazolate frameworks for hybrid supercapacitors - Zhang, Peng (2020)
Complex metal-organic frameworks used as precursors allow design and construction of various nanostructured functional materials which might not be accessible by other methods. Here, we develop a sequential chemical etching and sulfurization strategy to prepare well-defined double-shelled zinc-cobalt sulfide (Zn-Co-S) rhombic dodecahedral cages (RDCs). Yolk-shelled zinc/cobalt-based zeolitic imidazolate framework (Zn/Co-ZIF) RDCs are first synthesized by a controlled chemical etching process, followed by a hydrothermal sulfurization reaction to prepare double-shelled Zn-Co-S RDCs. Moreover, the strategy reported in this work enables easy control of the Zn/Co molar ratio in the obtained double-shelled Zn-Co-S RDCs. Owing to the structural and compositional benefits, the obtained double-shelled Zn-Co-S RDCs exhibit enhanced performance with high specific capacitance (1266 F g-1 at 1 A g-1 ), good rate capability and long-term cycling stability (91 % retention over 10,000 cycles) as a battery-type electrode material for hybrid supercapacitors.